Lipoprotein(a) and Cardiovascular Outcomes in Patients With Coronary Artery Disease and Different Metabolic Phenotypes - Jin, Jing-Lu; Zhang, Hui-Wen; Liu, Hui-Hui; Zhu, Cheng-Gang; Guo, Yuan-Lin; Wu, Na-Qiong; Xu, Rui-Xia; Dong, Qian; Li, Jian-Jun (Frontiers in Cardiovascular Medicine, 2022)
Background：The positive relation of metabolic healthy obesity (MHO) to cardiovascular risk is under debate in recent years. Previously, strong evidence supported the causal role of elevated plasma lipoprotein(a) [Lp(a)] levels in cardiovascular disease. The aim of the current study was to investigate the different associations of Lp(a) and cardiovascular events (CVEs) in patients with coronary artery disease (CAD) and different metabolic phenotypes. Methods: A total of 5089 patients who were angiography-proven CAD were consecutively included and followed up for CVEs. Obesity was defined as a body mass index (BMI) ≥25 kg/m2 according to Asia- specific BMI criteria. Patients were divided into four groups according to metabolic phenotypes which were metabolically healthy/unhealthy non-obese, and metabolically healthy/unhealthy obese (MHN, MHO, MUN, and MUO). Comparisons of CAD severity and outcomes were performed among four groups. Cox regression analyses and cubic spline models were used to assess the association of Lp(a) and CVEs in patients with different metabolic phenotypes. Results: During a median of 7.5 years’ follow-up, 540 (10.6%) CVEs occurred. MUN and MUO populations had more severe coronary stenosis than MHN ones while no significant difference in Gensini score was observed between MHN and MHO. Patients in MUN and MUO also presented higher risk of CVEs than that in MHN (HR :1.414, 95% CI :1.024-1.953–1.556 and HR :1.747, 95% CI :1.295-1.363, P <0.05). In subgroup analysis, restricted cubic spline models showed that no association between Lp(a) and CVEs existed in patients in MHN and MHO, but MUN and MUO groups presented increasing associations between Lp(a) and CVEs while such association was stronger in MUO group. In Cox regression analysis, Lp(a) >50 mg/dL was associated with 2.032-and 2.206-fold higher risk of subsequent CVEs in MUO and MUN subgroups respectively. Conclusion: Among patients with angiography-proven stable CAD, Lp(a) had more significant prognostic value in both MUO and MUN individuals regardless of obesity, suggesting the importance of screening of cardiovascular risk with Lp(a) in metabolic unhealthy patients.